GOOD CORPORATE GOVERNANCE PADA BUMN DI SUMATERA BARAT: GOOD CORPORATE GOVERNANCE IN STATE-OWNED ENTERPRISES IN WEST SUMATERA - Safitri Nelaz, Yolanda; Junita, Dewi (Universitas Riau, 2024)
Good Corporate Governance (GCG) is a system and process implemented by companies to ensure accountable, transparent, and responsible management. Effective GCG implementation can increase investors, stakeholders, and public trust in the company. This study aims to analyze the influence of these four variables on the implementation of GCG in companies. The research uses the Quesioner survey data collection method to BUMN in Padang, Indonesia. The data were then analyzed using multiple linear regression analysis. The results of this study showed that management commitment, internal audit competency and audit service quality have significant effect on GCG. However, the results of this study failed to prove the influence of organizational culture on GCG.